2011
DOI: 10.1007/s00122-011-1692-7
|View full text |Cite
|
Sign up to set email alerts
|

New broad-spectrum resistance to septoria tritici blotch derived from synthetic hexaploid wheat

Abstract: Septoria tritici blotch (STB), caused by the ascomycete Mycosphaerella graminicola, is one of the most devastating foliar diseases of wheat. We screened five synthetic hexaploid wheats (SHs), 13 wheat varieties that represent the differential set of cultivars and two susceptible checks with a global set of 20 isolates and discovered exceptionally broad STB resistance in SHs. Subsequent development and analyses of recombinant inbred lines (RILs) from a cross between the SH M3 and the highly susceptible bread wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
102
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 115 publications
6
102
0
2
Order By: Relevance
“…Khiar at the seedling and adult stages have shown that Z. tritici is governed by distinct factors, which is in accord with previous studies Tabib Ghaffary et al 2012;). The broad resistance in "Agili39" is mainly caused by the natural pyramiding of several QTLs with partial and major effects in the seedling and adult stage, which provide an improved fitness to withstand Z. tritici encounters.…”
Section: Genetic Makeup Of Durum Wheat Resistance To Stb: the Drasticsupporting
confidence: 80%
See 1 more Smart Citation
“…Khiar at the seedling and adult stages have shown that Z. tritici is governed by distinct factors, which is in accord with previous studies Tabib Ghaffary et al 2012;). The broad resistance in "Agili39" is mainly caused by the natural pyramiding of several QTLs with partial and major effects in the seedling and adult stage, which provide an improved fitness to withstand Z. tritici encounters.…”
Section: Genetic Makeup Of Durum Wheat Resistance To Stb: the Drasticsupporting
confidence: 80%
“…In bread wheat breeding, valuable genes for resistance have been identified and deployed that originate from wild ancestors (Mujeeb-Kazi et al 1996;Tabib Ghaffary et al 2012;Yang et al 2009). For instance, the Stb5 gene was identified in a synthetic hexaploid derived from T. turgidum ssp.…”
mentioning
confidence: 99%
“…The partial resistance is durable under field conditions and is expressed as a reduction in epidemic development (Chartrain et al, 2004). During the last decade 18 major resistance genes (Stb1-Stb18) to STB have been identified and mapped in the wheat genome (Arraiano et al, 2007;Goodwin, 2007;Chartrain et al, 2009;Tabib Ghaffary et al, 2011a;2011b). These developments have greatly improved the efficiency of marker-assisted selection in bread wheat.…”
Section: Introductionmentioning
confidence: 99%
“…As SHWs frequently carry unfavourable alleles and are agronomically poorly adapted, they are typically crossed and then back-or top-crossed to elite BWs to produce more agronomically acceptable synthetic derived lines (SDLs). Evaluation of SHWs and SDLs has revealed extensive new variation in morphological, physiological and agronomic traits (Villareal et al 1994a(Villareal et al , 1994bOrtiz et al 2007;Dreccer et al 2008;Rattey and Shorter 2010;Rattey et al 2011), in milling and baking quality traits (Kunert et al 2007), and in resistance to both biotic (Mujeeb-Kazi et al 2004;Ogbannaya et al 2008;Zwart et al 2010;Mulki et al 2013) and abiotic stresses (Ogbonnaya et al 2007;Rattey and Shorter 2010;De Leon et al 2011;Ghaffary et al 2012).…”
Section: Introductionmentioning
confidence: 99%